A graphic novel from the 4th International Symposium on the Effects of Climate Change on the World's Oceans. (16th November 2018) - Link, Jason S; Kohler, Bas; Griffis, Roger; Brady, Margaret M (Peg); Ito, Shin-Ichi; Garçon, Véronique; Hollowed, Anne; Barange, Manuel; Brown, Robin; Wawrzynski, Wojciech
Abstract: The world's oceans are changing in response to a changing climate, these changes have significant consequences, there is much at risk, and action is needed now to increase the resilience of ocean ecosystems and the people that depend on them. That was the message from the 4th International Symposium "Effects of Climate Change on the World's Oceans", held from 4 to 8 June 2018 in Washington, DC. The symposium gathered ∼650 people from over 50 countries to discuss not only how to advance our understanding and scientific knowledge, but also how to enact solutions based on that science to address challenges facing the world's oceans. Two perceptions were explored at the symposium: that we just do not know enough to act, and that there is nothing but bad news. The reality is that while better understanding of the causes and consequences of climate-related changes in ocean ecosystems is always useful, we already know enough to act. There are also opportunities, positive outcomes, and cause for hope in considering and communicating those actions. A professional graphic artist attended the meeting, and produced a range of amazingly insightful and often poignant cartoons as an effective means to share lessons from the conference in real time. As an entree into the special theme set, a selection of the cartoons has been assembled here, providing a narrative of the meeting and offering areas for future consideration.